The Present View of the Correlation of Breast Vascular Calcifications with Coronary Artery Calcifications - D. A. Bazhenova; O. S. Puchkova; E. A. Mershina; V. E. Sinitsyn (Вестник рентгенологии и радиологии, 2021)
Breast vascular calcifications are a manifestation of calcinosis of the medial layer of the artery walls. This type of calcifications is well visualized on mammograms. Mammography is a widespread and affordable screening test for breast cancer. The studies published in recent years demonstrate a relationship of breast vascular calcifications to cardiovascular risk factors, coronary heart disease. Identification of the correlation of breast vascular calcifications with coronary artery calcifications will be able to improve cardiovascular risk stratification in the group of women with an asymptomatic course.